Sentimen Analisa Ulasan Aplikasi Access by KAI pada Google Play Store menggunakan Algoritma K-NN - Jiana, Nur Afina; Hartono, Budi (Universitas Budi Darma, 2024)
Access by KAI is an application developed by PT. Kereta Api Indonesia (KAI) that plays an important role in simplifying the train ticket booking process for its users. The application has been downloaded more than 10 million times through the Google Play Store, with a review rating of 2.2 out of a scale of 1 to 5. This relatively low rating indicates a level of dissatisfaction among users. Moreover, the high number of negative reviews compared to positive reviews could also cause bias in the analysis results. Reviews from other users greatly influence the perception of the app's performance and quality among potential users. Therefore, this study aims to conduct a sentiment analysis of the application reviews published on the Google Play Store. The review data analyzed includes 1300 negative reviews and 457 positive reviews considered most relevant to provide a comprehensive overview of user perception. The method used in this analysis is the K-Nearest Neighbor (K-NN) Algorithm. The results of the study show an accuracy rate of 80%, a precision of 73%, a recall of 63%, and an f1-score of 65%. These findings are expected to provide insights for the app developers to improve the quality and performance of the Access by KAI application.